Project Report on Secure Digital Signature using Threshold Multisignature Scheme - ASHWEEJA H L, BHASKARA B, JAYAPRAKASH and VIJAYKUMAR (2010)
INTERNAL GUIDE: FANY BOURGIA R, MVJCE
Keywords: Threshold Multisignature Scheme